At the First Table : Food and Social Identity in Early Modern Spain - Campbell, Jodi, 1968- (Book collections on Project MUSE., 2017)
"At the First Table demonstrates the ways in which early modern Spaniards used food as a mechanism for the performance and maintenance of social identity"--